2017
DOI: 10.1080/13645706.2017.1418753
|View full text |Cite
|
Sign up to set email alerts
|

Insertion mechanics of bioinspired needles into soft tissues

Abstract: The reduction in the insertion force is due to the decrease in the friction force of the bioinspired needle with the bovine tissues, and its results are consistent with our previous results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…FIGURE 4 | (A) 3D bioinspired needles with specially designed barbs for decreasing insertion force (Sahlabadi et al, 2017). Reproduced with the permission of the Society of Medical Innovation and Technology, 2017.…”
Section: Cellular Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…FIGURE 4 | (A) 3D bioinspired needles with specially designed barbs for decreasing insertion force (Sahlabadi et al, 2017). Reproduced with the permission of the Society of Medical Innovation and Technology, 2017.…”
Section: Cellular Structuresmentioning
confidence: 99%
“…Reproduced with the permission of the Society of Medical Innovation and Technology, 2017. (B) Stinger needles, inspired by honeybee for decreasing tissue damage (Sahlabadi et al, 2017). Reproduced with the permission of 2018 by ASME.…”
Section: Cellular Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by these features, an early study demonstrated the feasibility of harpoon-shape notches in a silicon needle tip for insertion into a soft tissue phantom 27 . In experiments of insertion into the tissue-mimicking phantom 1 and the ex-vivo tissue 28 , the notched needle tips exhibited lower insertion forces when compared to the needle without notches. The insertion of a needle device with multiple incrementally moving needle components without the harpoon-shape notches was studied and showed the independent benefit of incremental motion to reduce the tissue phantom displacement during insertion 29 and allow deep insertion without buckling 30,31 .…”
mentioning
confidence: 94%
“…Study on interaction mechanics involving needle-tissue modeling, 2023 puncture force, 7,21 needle deflection, 20 tissue deformation, 24 mechanical behavior of tissue, 2527 and other aspects (e.g. force control algorithms) 2830 has been the research focus in the field of robot-assisted insertion.…”
Section: Introductionmentioning
confidence: 99%